1990
DOI: 10.1093/nar/18.5.1207
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic activities of overexpressed herpes simplex virus DNA polymerase purified from recombinant baculovirus-infected insect cells

Abstract: Biochemical characterization of the herpes simplex virus (HSV) DNA polymerase, a model DNA polymerase and an important target for antiviral drugs, has been limited by a lack of pure enzyme in sufficient quantity. To overcome this limitation, the HSV DNA polymerase gene was introduced into the baculovirus, Autographa californica nuclear polyhedrosis virus, under the control of the polyhedrin promoter to give rise to a recombinant baculovirus, BP58. BP58-infected Spodoptera frugiperda insect cells expressed a po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
61
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 39 publications
(32 reference statements)
5
61
0
Order By: Relevance
“…It has been reported [10,11] that the specific activity of the purified Pol is very similar to that of the DNA polymerase (PoI-UI.A2 protein heterodimer) isolated from HSV-l-infected mammalian cells. The conclusion drawn from this was that any stimulatory activity by the UIA2 protein on the Pol activity was slight, in contrast to the results of Gallo and co-workers [fl], although the UIA2 protein was found to increase the processivity of the polymerisation ([I0], A. Owsianka and H.S.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…It has been reported [10,11] that the specific activity of the purified Pol is very similar to that of the DNA polymerase (PoI-UI.A2 protein heterodimer) isolated from HSV-l-infected mammalian cells. The conclusion drawn from this was that any stimulatory activity by the UIA2 protein on the Pol activity was slight, in contrast to the results of Gallo and co-workers [fl], although the UIA2 protein was found to increase the processivity of the polymerisation ([I0], A. Owsianka and H.S.…”
Section: Introductionmentioning
confidence: 87%
“…The reported activation [8] was observed under high salt conditions (100 mM Tris buffer, pH 8.0, 200 mM KCi), while lack of any effect [10,11] was found under conditions (20 mM Tris-HCl, pH 7.5, 150 mM (NH~)2SO~) that seem similar to those (75 mM Tris-HCl, pH 7.5, 70 mM (NH4)2SO4; Fig. 1) under which the UL42 protein has little or no effect on the polymerasc activity of Pol.…”
Section: Effect Of Salt Concentration On Dna Polymerase Ac Tivity Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, six of the replication proteins have already been expressed in a functional form in Spodoptera frugiperda (SO insect cells infected with appropriate (AcNPV) recombinants (Olivo et al, 1988;Dodson et al, 1989;Gottlieb et al, 1990;Marcy et al, 1990;Calder & Stow, 1990). Because many future efforts are aimed at utilizing these heterologously expressed proteins in cell-free systems, it is important that they should be able to perform all the replicative functions normally carried out by their counterparts during a lytic infection of permissive cells, and not merely those activities for which convenient assays are presently available.…”
Section: Introductionmentioning
confidence: 99%
“…Viruses in this family encode most of the proteins essential for and directly involved in DNA replication (2)(3)(4), including a well conserved DNA polymerase catalytic subunit (pol), which is a member of the polymerase B family (5,6). HSV-1 pol possesses 5Ј-to 3Ј-polymerizing and 3Ј-to 5Ј-exonuclease (exo) activities (7,8), the latter of which is involved in the removal of incorrectly incorporated deoxyribonucleoside triphosphates (9 -12). The importance of this proofreading activity for maintaining fidelity of DNA replication was suggested by studies from our laboratory that demonstrated the relatively poor ability of HSV-1 pol to discriminate between the correct and incorrect nucleotide for incorporation in single turnover experiments (13).…”
mentioning
confidence: 99%